A comparative analysis of game load and game results in elite collegiate basketball players over a regular season - Imal, O.; Fallon Verbruggen, F.; Maly, T.; Stephenson, C.; Zahalka, F.; Petway, A. (International Journal of Sports Science & Coaching, 2025)
This study examines external game load parameters and game results in elite collegiate basketball players, with a focus on game-intensity and positional differences. Fourteen male collegiate basketball players (average age: 22.5 ± 1.8 years) were tracked using wearable GPS indoor system devices (Catapult Sports, Catapult T7, Melbourne, Australia) across a 30-game college basketball regular season. Games were categorized by point differentials: Wins by =10 points, Wins by <10 points, Losses by <10 points, and Losses by =10 points. Descriptive statistics, Pearson correlations, and stepwise regression analyses were used to explore relationships between external load parameters and game results, with additional analysis by player position (Guard, Forward, Center). Significant correlations were found between High-Intensity Player Load/Min (HIPL/Min) (r = 0.278, p < 0.001) and Points Scored/Min (PS/Min) (r = 0.270, p < 0.001) with score difference, indicating their importance in influencing game results. HIPL/Min alone explained 7.2% of the variance in score difference. These findings suggest that optimizing HIPL could maximize tactical efficiency and PS, which could improve game performance and inform training and match-play strategies in basketball. Future research should investigate additional variables such as internal load and mechanical factors to provide a fuller picture of performance dynamics.